The Role of Peat Layers on Iron Dynamics in Peatlands - Fahmi, Arifin; Radjagukguk, Bostang; Purwanto, Benito Heru; Hanudin, Eko (JOURNAL OF TROPICAL SOILS, 2010)
The Role of Peat Layers on Iron Dynamics in Peatlands (A Fahmi, B Radjagukguk, BH Purwanto and E Hanudin): The research aimed to study the effect of peat thickness and humification stage of the peat material on Fe solubility at the peatlands with sulfidic material as substratum.  The research was conducted at three conditionals of ombrogen peatlands ie ; deep, moderate and shallow peat. Soil samples were collected by using peat borer according to interlayer (the border layer of peat and mineral layer) and conditional of soil horizons.  The sample point depth were (cm) G.s2 : 25, G.s1 : 50, Int.s : 70,  M.s1 : 90 and M.s2 : 100 for shallow peat, G.m2 : 47, G.m1 : 100, Int.m : 120 and M.m1 : 135 for moderate peat and G.d3 : 50, G.d2 : 150, G.d1 : 200, Int.d : 220  and M.d1 : 235 for deep peat respectively.  The results showed that most of Fe on the tested soils was found in organic forms. The peat layers above the sulfidic material decreased the Fe2+ solubility at peatlands. Fe2+ concentration in peat layer decreased with its increasing distance from sulfidic material. There was any other processes beside complexation and chelation of  Fe2+  by humic material and its processes was reduction of Fe3+ and this conditions was reflected in redox potential values (Eh).